PEMBENTUKAN KARAKTER MAHASISWA UNIVERITAS NEGERI JAKARTA (UNJ) SESUAI AJARAN AL-QUR'AN - Rivani Ayu Ningsih; Muhammad Andre Maynard Musnamar; Nazwa Mutia Violita; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
This article discusses how the teachings of the Qur'an can shape the character of an individual, especially in a campus environment. Character does not just appear in a Muslim, in its formation it requires guidelines and instructions. Various problems regarding negative characters are often widely displayed as if they are right to do. Such as bullying, corruption, Domestic Violence, and others. These various problems require character education that can truly create positive characters.